Effects of substrate microstructure on biomimetic unit properties and wear resistance of H13 steel processed by laser remelting. (October 2018) - Zang, Chuanlong; Zhou, Ti; Zhou, Hong; Yuan, Yuhuan; Zhang, Peng; Meng, Chao; Zhang, Zhihui
Highlights: Laser bionic units were processed on a variety of H13 substrate microstructure. Substrate microstructure of H13 steel affects unit properties. The differences and regularities of the units were compared and discussed. Microhardness and wear resistance were improved to various degrees. Abstract: To improve the service life of H13 steel with different substrate microstructures, the bionic coupling units of H13 steel were manufactured by laser remelting on four types of heat treatment surface. The differences and regularities in the size, microstructure, grain size, hardness and wear resistance of the units were compared and discussed. The results demonstrated that the cross-sectional area and grain size of the units were enlarged with the increase of austenite nucleation ability of the substrate microstructure, but the degree of micro-hardness improvement was reduced. Meanwhile, its micro-hardness and the corresponding wear resistance were improved to varying degrees. In particular, the improvement of the annealed state was the highest, as the micro-hardness and wear resistance were enhanced by 165.57% and 39.10%, respectively.